Al-Manhaj al-Usuli li al-Imam Salih al-Maqbali fi Kitabihi: ?Najah al-Talib Hashiah ?ala Mukhtasar al-Muntaha li Ibn Hajib? - Al-Nahari, Ameen Ahmed Abdullah Qasem; Ali, Abdul Karim (Jurnal Fiqh, 2012)
Imam Salih al-Maqbali, as well-known mujtahid of the eleventh-century of Hijrah, is known by his Ijtihad, which is recognized by respectable Muslim scholars. This article attempts to explain Imam al-Maqbali?s personal background, to elucidate his methodology, and to analyse his methodology of al Istidlal. In order to achieve these objectives, this article uses a historical method to clarify al-Maqbali?s account and deductive method to determine his methodology. The study concludes that most problems advanced by Imam al-Maqbali have considerable impact. His approach is independent and not fanatical but thorough judgment against others. It also found that he used weak hadis (hadith da?if) to support his arguments.